The Impact of Fisheries Extension Services on Fish Farming Businesses in Palembang City - Siska Almaniar; Waliah Nur Rahayu; Junainah; Tiara Santeri; Rismarini (Journal of Global Sustainable Agriculture, 2026)
Knowledge related to operational practices and business development strategies for fish farmers is crucial for the sustainability of the aquaculture sector, including in Palembang City as one of the main centers for freshwater fish farming. This study aims to evaluate the impact of extension services on operational practices and business development strategies for fish farmers in Palembang. The survey was conducted from July to September 2025 on 100 respondents with the criteria of at least three years of fish farming experience and having participated in extension activities. Data were collected through structured interviews, observations, and focus group discussions, then analyzed descriptively and using Spearman's Rank correlation. The results showed that extension services improved operational behavior (average score of 60.73; high category), especially in feed management and water quality, although business recording was still moderate. The impact on business development was also high (average score of 61.06), especially on production efficiency and market access, while business diversification and institutional strengthening were classified as moderate. The results of the Spearman's rho correlation test showed a value of 0.716, which means there is a positive and strong relationship between the quality of extension services and improved operational behavior and business development. These findings confirm that fisheries extension workers play a strategic role in promoting production efficiency, business innovation, and improving the managerial capacity of farmers. However, business sustainability will be more optimal if the administrative and institutional aspects of the groups are systematically strengthened